Additive manufacturing: A growing platform to replace, reduce and refine animal experiments (Transactions on Additive Manufacturing Meets Medicine, 2019)
Replacement, Reduction and Refinement (3Rs) are the bedrock of animal experiments and additive manufacturing (AM) fortifies these principles. To evaluate the accuracy of 3D models, we built skeletal models of rabbit head, based on Micro-Magnetic Radiation Imaging (uMRI) and Micro-Computed Tomography (uCT). Data was segmented using a computer software and the reconstructed stereolithography file was printed in 1:1 scaled model using a polyjet printer. Point-based part comparison analysis (PCA) was performed to gauge its dimensional accuracy. The results displayed that AM-workflow is an accurate process for reproducing life size skeletal models, however support material cleaning requires further research.